Plasmonic Stripes in Aqueous Environment Co-Integrated With Si3N4 Photonics - George Dabos; Dimitra Ketzaki; Athanasios Manolis; Laurent Markey; Jean Claude Weeber; Alain Dereux; Anna Lena Giesecke; Caroline Porschatis; Bartos Chmielak; Dimitris Tsiokos; Nikos Pleros (IEEE Photonics Journal, 2018)
We demonstrate the design, fabrication, and the experimental characterization of gold-based plasmonic stripes butt-coupled with low-pressure-chemical-vapor-deposition (LPCVD)-based Si3N4 waveguides for the excitation of surface-plasmon-polariton (SPP) modes in aqueous environment. Plasmonic gold stripes, in aqueous environment, with cross-sectional dimensions of 100 nm × 7 μm were interfaced with 360 nm × 800 nm Si3N4 waveguides cladded with low-temperature-oxide, exploiting linear photonic tapers with appropriate vertical (VO) and longitudinal (LO) offsets between the plasmonic and photonic waveguide facets. An interface insertion loss of 2.3 ± 0.3 dB and a plasmonic propagation length ( $L_{{\rm{spp}}}$ ) of 75 μ m have been experimentally measured at 1.55 μm for a VO of 400 nm and an LO of 500 nm, with simulation results suggesting high tolerance to VO and LO misalignment errors. The proposed integration approach enables seamless co-integration of plasmonic stripes, in aqueous environment, with a low-loss and low-cost LPCVD-based Si3N4 waveguide platform, revealing its strong potential for future employment in biochemical sensing applications.